Electrochemical Behavior of Phosphine Induced Anode Performance Degradation in a Planar SOFC: A Numerical Study. (2nd June 2015) - Sezer, Hayri; Celik, Ismail Bektas; Yang, Tao
Abstract : A one-dimensional model was developed to predict the performance degradation of the SOFCs anode exposure of fuel contaminants found in typical coal syngas. This model is extended to a three-dimensional model to predict the phosphine induced performance degradation in relatively large planar cells operating on hydrogen. The model parameters are calibrated using button cell experiments conducted under accelerated tests conditions. These parameters are then used to perform simulations to predict fuel contaminant performance degradation of planar cells. The results from degradation simulations show that the contaminant coverage alter the initial current distribution, as well as the fuel and oxygen distribution inside the anode significantly. The electrochemical characteristic of the degraded cell is analyzed by performing impedance and polarization simulations at cell operating current. The polarization and impedance simulations are implemented by dividing the cell into three regions along the fuel flow direction. The results show that the degradation rates and the impedance behavior of planar cells are very different than those observed in button cells.